Preparation method of high-purity alumina ceramic electrostatic chuck

By optimizing the process steps and conditions, the problems of uneven density of the aluminum oxide ceramic electrostatic chuck and material defects are solved, and the high density, mechanical strength and electrical insulation performance of the ceramic are improved, and the stability and reliability of the electrostatic suction cup are improved.

CN119912241APending Publication Date: 2025-05-02JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411884279.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, when preparing high-performance alumina ceramic electrostatic chucks, there are uneven density and material defects, which are difficult to meet the high purity and high mechanical strength requirements of the electrostatic suction cup.

Method used

The process steps such as ball milling, defoaming, casting, preparation of electrodes, drilling, lamination, glue discharge, sintering, leveling and thermal isostatic pressure treatment are adopted to optimize the temperature and pressure conditions, control the heating and cooling rate, and ensure the high purity and high performance of the ceramic.

Benefits of technology

It significantly improves the density and mechanical strength of the ceramic, improves transparency, enhances electrical insulation performance, and improves the stability and reliability of the electrostatic suction cup.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912241A_ABST
    Figure CN119912241A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-purity alumina ceramic electrostatic chuck, which belongs to the technical field of electrostatic chucks, and comprises the following steps: a) preparing alumina slurry; b) defoaming the alumina slurry; c) tape casting; d) preparing an electrode; e) punching; f) laminating; g) discharging glue; h) sintering: performing high-temperature sintering on the ceramic green body after glue discharging; i) leveling: carrying out leveling treatment on the sintered ceramic main body; j) hot isostatic pressing treatment: the leveled ceramic main body is placed in hot isostatic pressing equipment to be treated at high temperature and high pressure, gas used for hot isostatic pressing treatment is inert gas, and the inert gas is argon or nitrogen or mixed gas of the argon and the nitrogen, so that the influence of oxidation or reduction reaction on the purity and performance of the ceramic is avoided; the treatment temperature is 1200-1600 DEG C, the pressure is 100-200 MPa, and the duration time is 1-6 hours, so that the compactness and the mechanical strength of the ceramic are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for preparing a high-purity alumina ceramic electrostatic chuck. Background Art

[0002] Electrostatic chuck (ESC) is a device that uses electrostatic force to absorb objects. It is widely used in high-precision fields such as semiconductor manufacturing, optoelectronics industry, and flat panel display. In the semiconductor manufacturing process, electrostatic chucks are used to fix silicon wafers for various processing operations, including etching, thin film deposition, etc. In these processes, stable fixation of the substrate is the key factor to ensure processing accuracy, so extremely high requirements are placed on the material, design, and manufacturing process of the electrostatic chuck. The main function of the electrostatic chuck depends on the characteristics of the dielectric material, so the requirements for the material include:

[0003] 1. High purity: Impurities in the material may affect the performance of the dielectric, and thus affect the adsorption effect and processing accuracy.

[0004] 2. High mechanical strength: It needs to be able to withstand the physical stress generated during the processing.

[0005] 3. Excellent thermal stability: The semiconductor manufacturing process is often accompanied by high-temperature processes, requiring the chuck to maintain stable performance at high temperatures. Alumina ceramics have become one of the ideal materials for manufacturing electrostatic chucks due to its excellent insulation properties, high temperature resistance and high mechanical strength.

[0006] However, the traditional manufacturing process is still difficult to meet the performance requirements of electrostatic chucks in terms of purity and strength. Therefore, the use of more advanced processes, such as hot isostatic pressing (HIP) technology, has gradually become a trend. Hot isostatic pressing (HIP) is a process that densifies materials under high temperature and high pressure conditions. The working principle of this process is to place the material to be processed in an atmosphere of high temperature (usually over 1000°C) and high pressure (typical pressure is 100-200MPa), and at the same time uniformly apply isostatic pressure to the surrounding areas, thereby eliminating pores or defects inside the material, greatly improving the density, mechanical strength and durability of the material. For high-purity alumina ceramics, the HIP process can effectively improve its mechanical strength, thermal stability and electrical insulation properties, making it an ideal method for manufacturing high-performance electrostatic chucks. However, in order to ensure the high purity and high performance of alumina ceramics, the parameter control requirements of the HIP process are very precise, including temperature, pressure, and insulation time. The complexity of the process increases the technical threshold and failure rate of production. In the prior art, as mentioned in Chinese patent CN103571287A, the method for preparing high-performance alumina ceramics by HIP process has problems of uneven density and material defects. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing a high-purity alumina ceramic electrostatic chuck, which can improve the density and mechanical strength of the electrostatic chuck and improve the transparency.

[0008] In order to solve the above technical problems, the technical solution of the present invention is:

[0009] A method for preparing a high-purity alumina ceramic electrostatic chuck, the method comprising:

[0010] a) Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant, and a solvent, and ball milled to prepare an alumina slurry with a uniform particle size distribution. The ball milled slurry passes through a filter and enters a degassing tank;

[0011] b) Degassing: The bubbles in the slurry are discharged by stirring and vacuum treatment for 2 to 6 hours, and the slurry is then filtered and enters the casting machine;

[0012] c) Tape casting: The slurry is spread into a film on a tape casting machine through a tape casting process to form a ceramic body, the thickness of the ceramic body is between 50 and 500 microns, and the required thickness is controlled by adjusting the gap between the tape casting blades and the viscosity of the slurry;

[0013] d) preparing electrodes: forming an electrode layer inside the ceramic to generate adsorption force, and preparing the electrodes by any one of screen printing, sputtering deposition, evaporation and pressing;

[0014] e) Punching: electrode through holes and other holes required by the design are reserved on the formed ceramic body. The diameter and position of the holes are precisely controlled according to the design of the electrodes and connectors to ensure that the holes are aligned with the electrodes after lamination;

[0015] f) Lamination: Align and laminate the multi-layer ceramic film with the electrode layer to form a multi-layer ceramic body, and laminate by any one of mechanical lamination, hot pressing lamination, WIP, and vacuum lamination to ensure that each layer of the ceramic film is accurately aligned with the electrode layer, and the laminated structure forms a stable laminate under heating and pressing;

[0016] g) Debinding: The multi-layered ceramic body is placed in a debinding furnace for heating to remove organic binders and adhesives. The debinding is carried out at 300°C to 600°C for 50 to 100 hours.

[0017] h) Sintering: The ceramic body after debinding is sintered at high temperature in a vacuum, inert gas environment or reducing gas environment. The sintering temperature is 1400℃~1800℃ and the holding time is 2~6h to prevent oxidation and sinter into porcelain, ensure the high purity and high performance of the ceramic, and form a densified ceramic body;

[0018] i) Leveling: The sintered ceramic body is leveled to make the surface of the ceramic body flat, which is achieved by mechanical grinding and polishing or pressing. The flatness is 50-500um, which reduces the pre-flatness and makes it possible to better improve the flatness in the subsequent steps;

[0019] j) Hot isostatic pressing: The flattened ceramic body is placed in a hot isostatic pressing device and processed under high temperature and high pressure. The gas used in the hot isostatic pressing is an inert gas, which is argon or nitrogen or a mixture of the two, to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The processing temperature is 1200°C to 1600°C, the pressure is 100 to 200 MPa, and the duration is 1 to 6 hours to further improve the density and mechanical strength of the ceramic.

[0020] Preferably, in the hot isostatic pressing step, the processing temperature is 1400° C. to 1600° C., the pressure is 140 to 180 MPa, and the duration is 2 to 6 hours, so as to further improve the density and mechanical strength of the ceramic.

[0021] Preferably, in the hot isostatic pressing step, the processing temperature is 1500° C., the pressure is 150 MPa, and the duration is 4 hours, so as to further improve the density and mechanical strength of the ceramic.

[0022] The above technical solution has the following beneficial effects:

[0023] 1. Improve the density of ceramics:

[0024] By optimizing the temperature and pressure conditions, the HIP process can significantly reduce the pores in alumina ceramics and improve the density of ceramics, ultimately making the relative density of ceramics reach or exceed 99.9%. High-density ceramics not only improve mechanical strength, but also enhance their electrical insulation properties, which helps to improve the stability and reliability of the suction cup during electrostatic adsorption.

[0025] 2. Enhance the hardness of ceramics:

[0026] By controlling the heating rate and pressure, lattice defects or residual stresses inside the material are avoided, so that the ceramics can obtain higher hardness, which makes the electrostatic chuck more wear-resistant and can operate stably for a long time in harsh process environments;

[0027] 3. Improve mechanical strength:

[0028] By optimizing the temperature and cooling rate, the HIP process can reduce microcracks and internal stress in ceramics, effectively improving the fracture toughness and mechanical strength of ceramics, usually reaching more than 700MPa. The higher mechanical strength makes the electrostatic chuck more reliable when subjected to external stress (such as thermal cycles, mechanical vibrations, etc.), thereby extending the service life of the product.

[0029] 4. Improve the transparency of ceramics:

[0030] Controlling the heating and cooling process of the HIP process can make the grain structure of alumina ceramics more uniform, reduce impurities and defects at the grain boundaries, and thus improve the optical transparency of the ceramics. Higher transparency is not only conducive to more precise control of the adsorption performance of the electrostatic chuck, but also provides added value in certain optical applications.

[0031] 5. Improve electrical insulation performance:

[0032] By strictly controlling the impurity content and temperature treatment in the HIP process, the conductive impurities in the material can be further reduced, so that the alumina ceramic can maintain high purity, which helps to improve the electrical insulation performance of the electrostatic chuck and ensure that it can provide stable electric field control and adsorption effects during the semiconductor manufacturing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of Example 1 of the present invention;

[0034] Figure 2 This is the SEM image of Example 2 of the present invention;

[0035] Figure 3 This is the SEM image of Example 3 of the present invention;

[0036] Figure 4 This is the SEM image of Example 4 of the present invention;

[0037] Figure 5 This is the SEM image of Example 5 of the present invention;

[0038] Figure 6 This is the SEM image of Example 6 of the present invention;

[0039] Figure 7 This is the SEM image of Example 7 of the present invention. DETAILED DESCRIPTION

[0040] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0041] A method for preparing a high-purity alumina ceramic electrostatic chuck comprises the following steps:

[0042] Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant, and a solvent, and ball milled to prepare an alumina slurry with a uniform particle size distribution. The ball milled slurry passes through a filter and enters a degassing tank;

[0043] Degassing: The bubbles in the slurry are discharged by stirring and vacuum treatment for 2 to 6 hours, and the slurry is then filtered into the casting machine. In other embodiments of this embodiment, the stirring and vacuum treatment time is 2 hours or 6 hours, or 4 hours;

[0044] Tape casting: The slurry is spread into a film on a tape casting machine through a tape casting process to form a ceramic body, the thickness of the ceramic body is between 50 and 500 microns, and the required thickness is controlled by adjusting the gap between the tape casting blades and the viscosity of the slurry; in other implementations of this embodiment, the thickness of the ceramic body is 50 microns or 500 microns, or 250 microns, and the specific size is selected according to needs or design requirements;

[0045] Preparation of electrodes: forming an electrode layer inside the ceramic to generate adsorption force, and using any one of screen printing, sputtering deposition, evaporation, and pressing methods to prepare the electrodes;

[0046] Punching: electrode through holes and other holes required by the design are reserved on the formed ceramic body. The diameter and position of the holes are precisely controlled according to the design of the electrodes and connectors to ensure that the holes are aligned with the electrodes after lamination.

[0047] Lamination: Align and laminate the multi-layer ceramic film with the electrode layer to form a multi-layer ceramic body. Use any of the following methods: mechanical lamination, hot pressing lamination, WIP, or vacuum lamination to ensure that each layer of the ceramic film is accurately aligned with the electrode layer. The laminated structure forms a stable laminate under heating and pressing.

[0048] Debinding: The multilayer ceramic body is placed in a debinding furnace for heating to remove organic binders and adhesives. The debinding is performed at 300°C to 600°C for 50 to 100 hours. In other embodiments of the present embodiment, the debinding is performed at 300°C or 600°C for 50 hours or 100 hours, or at 450°C for 80 hours.

[0049] Sintering: The ceramic body after debinding is subjected to high-temperature sintering in a vacuum, inert gas environment or reducing gas environment, with a sintering temperature of 1400°C to 1800°C and a holding time of 2 to 6 hours to prevent oxidation and sinter into porcelain, thereby ensuring high purity and high performance of the ceramic and forming a densified ceramic body; in other implementations of this embodiment, the sintering temperature is 1400°C or 1800°C, the holding time is 2 hours or 6 hours, or the sintering temperature may be 1650°C, and the holding time is 5 hours;

[0050] Leveling: The sintered ceramic body is leveled to make the surface of the ceramic body flat, which is achieved by mechanical grinding and polishing or pressing, with a flatness of 50 to 500um, reducing the pre-flatness so that the subsequent steps may better improve the flatness; in other implementations of this embodiment, the flatness of the ceramic body after sintering is 50um or 500um, or 350um;

[0051] Hot isostatic pressing treatment: placing the flattened ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used for hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two, to avoid the influence of oxidation or reduction reaction on the purity and performance of the ceramic, the treatment temperature is 1200°C to 1600°C, the pressure is 100 to 200 MPa, and the duration is 1 to 6 hours, so as to further improve the density and mechanical strength of the ceramic; in other implementations of this embodiment, the hot isostatic pressing treatment temperature is 1200°C or 1600°C, the pressure is 100 MPa or 200 MPa, and the duration is 1 hour or 6 hours;

[0052] Preferably, in the hot isostatic pressing step, the processing temperature is 1400° C. to 1600° C., the pressure is 140 to 180 MPa, and the duration is 2 to 6 hours to further improve the density and mechanical strength of the ceramic; in other implementations of this embodiment, the hot isostatic pressing temperature is 1400° C. or 1600° C., the pressure is 140 MPa or 180 MPa, and the duration is 2 hours or 6 hours;

[0053] More preferably, in the hot isostatic pressing step, the processing temperature is 1500° C., the pressure is 150 MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic;

[0054] The technical solution of this application has the following advantages:

[0055] 1. Improve the density of ceramics:

[0056] By optimizing the temperature and pressure conditions, the HIP process can significantly reduce the pores in alumina ceramics and improve the density of ceramics, ultimately making the relative density of ceramics reach or exceed 99.9%. High-density ceramics not only improve mechanical strength, but also enhance their electrical insulation properties, which helps to improve the stability and reliability of the suction cup during electrostatic adsorption.

[0057] 2. Enhance the hardness of ceramics:

[0058] By controlling the heating rate and pressure, lattice defects or residual stresses inside the material are avoided, so that the ceramics can obtain higher hardness, which makes the electrostatic chuck more wear-resistant and can operate stably for a long time in harsh process environments;

[0059] 3. Improve mechanical strength:

[0060] By optimizing the temperature and cooling rate, the HIP process can reduce microcracks and internal stress in ceramics, effectively improving the fracture toughness and mechanical strength of ceramics, usually reaching more than 700MPa. The higher mechanical strength makes the electrostatic chuck more reliable when subjected to external stress (such as thermal cycles, mechanical vibrations, etc.), thereby extending the service life of the product.

[0061] 4. Improve the transparency of ceramics:

[0062] Controlling the heating and cooling process of the HIP process can make the grain structure of alumina ceramics more uniform, reduce impurities and defects at the grain boundaries, and thus improve the optical transparency of the ceramics. Higher transparency is not only conducive to more precise control of the adsorption performance of the electrostatic chuck, but also provides added value in certain optical applications.

[0063] 5. Improve electrical insulation performance:

[0064] By strictly controlling the impurity content and temperature treatment in the HIP process, the conductive impurities in the material can be further reduced, so that the alumina ceramic can maintain high purity, which helps to improve the electrical insulation performance of the electrostatic chuck and ensure that it can provide stable electric field control and adsorption effects during the semiconductor manufacturing process.

[0065] Example 1

[0066] refer to Figure 1, a method for preparing a high-purity alumina ceramic electrostatic chuck, comprising the following steps:

[0067] Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant, and a solvent, and ball milled to prepare an alumina slurry with a uniform particle size distribution. The ball milled slurry passes through a filter and enters a degassing tank;

[0068] Degassing: The bubbles in the slurry are discharged by stirring and vacuum treatment for 4 hours, and the slurry is then filtered and enters the casting machine;

[0069] Tape casting: The slurry is spread into a film on a tape casting machine through a tape casting process to form a ceramic body. The thickness of the ceramic body is 250 microns. The required thickness is controlled by adjusting the gap between the tape casting blades and the viscosity of the slurry.

[0070] Preparation of electrodes: forming an electrode layer inside the ceramic to generate adsorption force, and using any one of screen printing, sputtering deposition, evaporation, and pressing methods to prepare the electrodes;

[0071] Punching: electrode through holes and other holes required by the design are reserved on the formed ceramic body. The diameter and position of the holes are precisely controlled according to the design of the electrodes and connectors to ensure that the holes are aligned with the electrodes after lamination.

[0072] Lamination: Align and laminate the multi-layer ceramic film with the electrode layer to form a multi-layer ceramic body. Use any of the following methods: mechanical lamination, hot pressing lamination, WIP, or vacuum lamination to ensure that each layer of the ceramic film is accurately aligned with the electrode layer. The laminated structure forms a stable laminate under heating and pressing.

[0073] Debinding: The multi-layered ceramic body is placed in a debinding furnace for heating to remove organic binders and adhesives. The debinding is carried out at 450°C for 80 hours.

[0074] Sintering: The ceramic body after debinding is sintered at high temperature in a vacuum, inert gas environment or reducing gas environment. The sintering temperature is 1650℃ and the holding time is 5h to prevent oxidation and sinter into porcelain, ensuring the high purity and high performance of the ceramic and forming a densified ceramic body.

[0075] Leveling: The sintered ceramic body is leveled to make the surface of the ceramic body flat. This is achieved by mechanical grinding and polishing or pressing. The flatness is 350um, which reduces the pre-flatness and makes it possible to better improve the flatness in subsequent steps.

[0076] This embodiment was not subjected to hot isostatic pressing. Figure 1 , the light transmittance of the ceramic body prepared in this embodiment is 0.

[0077] Example 2

[0078] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0079] refer to Figure 2 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two, to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1300°C, the pressure is 150MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic.

[0080] Example 3

[0081] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0082] refer to Figure 3 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two, to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1400°C, the pressure is 150MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic.

[0083] Example 4

[0084] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0085] refer to Figure 4 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1500°C, the pressure is 150MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic.

[0086] Example 5

[0087] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0088] refer to Figure 5 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1600°C, the pressure is 150MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic.

[0089] Example 6

[0090] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0091] refer to Figure 6 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1500°C, the pressure is 170MPa, and the duration is 4 hours to further improve the density and mechanical strength of the ceramic.

[0092] Example 7

[0093] On the basis of Example 1, a hot isostatic pressing treatment is added, and the ceramic body is flattened after sintering, and then hot isostatic pressing treatment is performed again after flattening;

[0094] refer to Figure 7 The hot isostatic pressing treatment includes: placing the leveled ceramic body in a hot isostatic pressing device and treating it under high temperature and high pressure, wherein the gas used in the hot isostatic pressing treatment is an inert gas, which is argon or nitrogen or a mixture of the two to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The treatment temperature is 1500°C, the pressure is 170MPa, and the duration is 6 hours to further improve the density and mechanical strength of the ceramic.

[0095] The results of the above embodiments are shown in Table 1 below:

[0096] Table 1:

[0097]

[0098] By analyzing the data in Table 1, we can know the influence of HIP conditions on density:

[0099] The main effect of temperature: In the temperature range of 1300℃ to 1500℃, the increase in temperature helps the densification of the material and improves the density, but too high a temperature (such as 1600℃) does not further improve the density;

[0100] The influence of pressure is small: the increase of pressure does not significantly improve the density of the material, and may even have an adverse effect on the density of the material outside a certain pressure range.

[0101] Process optimization: 4 hours of treatment at 1500°C and 150Mpa is the best condition, which can achieve high-density materials with good light transmittance and mechanical properties.

[0102] Effect of HIP on hardness and light transmittance:

[0103] Temperature has a great influence on hardness and light transmittance: at higher temperatures (such as 1500°C), both hardness and light transmittance reach their optimal state, but too high a temperature (such as 1600°C) may cause a decrease in material performance, especially light transmittance.

[0104] The increase in pressure is detrimental to performance: when the temperature is maintained at 1500°C, a higher pressure (such as 170Mpa) does not further improve the hardness and light transmittance of the material, but has a certain negative effect.

[0105] The optimal HIP conditions are 1500°C, 150Mpa, and 4 hours. At this time, the material has the best hardness and light transmittance, and is suitable for application scenarios that require high strength and high transparency.

[0106] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a high-purity alumina ceramic electrostatic chuck, characterized in that: The method comprises: a) Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant, and a solvent, and ball milled to prepare an alumina slurry with a uniform particle size distribution. The ball milled slurry passes through a filter and enters a degassing tank; b) Degassing: The bubbles in the slurry are discharged by stirring and vacuum treatment for 2 to 6 hours, and the slurry is then filtered and enters the casting machine; c) Tape casting: The slurry is spread into a film on a tape casting machine through a tape casting process to form a ceramic body, the thickness of the ceramic body is between 50 and 500 microns, and the required thickness is controlled by adjusting the gap between the tape casting blades and the viscosity of the slurry; d) preparing electrodes: forming an electrode layer inside the ceramic to generate adsorption force, and preparing the electrodes by any one of screen printing, sputtering deposition, evaporation and pressing; e) Punching: electrode through holes and other holes required by the design are reserved on the formed ceramic body. The diameter and position of the holes are precisely controlled according to the design of the electrodes and connectors to ensure that the holes are aligned with the electrodes after lamination; f) Lamination: Align and laminate the multi-layer ceramic film with the electrode layer to form a multi-layer ceramic body, and laminate by any one of mechanical lamination, hot pressing lamination, WIP, and vacuum lamination to ensure that each layer of the ceramic film is accurately aligned with the electrode layer, and the laminated structure forms a stable laminate under heating and pressing; g) Debinding: The multi-layered ceramic body is placed in a debinding furnace for heating to remove organic binders and adhesives. The debinding is carried out at 300°C to 600°C for 50 to 100 hours. h) Sintering: The ceramic body after debinding is sintered at high temperature in a vacuum, inert gas environment or reducing gas environment. The sintering temperature is 1400℃~1800℃ and the holding time is 2~6h to prevent oxidation and sinter into porcelain, ensure the high purity and high performance of the ceramic, and form a densified ceramic body; i) Leveling: The sintered ceramic body is leveled to make the surface of the ceramic body flat, which is achieved by mechanical grinding and polishing or pressing. The flatness is 50-500um, which reduces the pre-flatness and makes it possible to better improve the flatness in the subsequent steps; j) Hot isostatic pressing: The flattened ceramic body is placed in a hot isostatic pressing device and processed under high temperature and high pressure. The gas used in the hot isostatic pressing is an inert gas, which is argon or nitrogen or a mixture of the two, to avoid the influence of oxidation or reduction reactions on the purity and performance of the ceramic. The processing temperature is 1200°C to 1600°C, the pressure is 100 to 200 MPa, and the duration is 1 to 6 hours to further improve the density and mechanical strength of the ceramic.

2. The method for preparing a high-purity alumina ceramic electrostatic chuck according to claim 1, characterized in that: In the hot isostatic pressing step, the processing temperature is 1400° C. to 1600° C., the pressure is 140 to 180 MPa, and the duration is 2 to 6 hours, so as to further improve the density and mechanical strength of the ceramic.

3. The method for preparing a high-purity alumina ceramic electrostatic chuck according to claim 2, characterized in that: In the hot isostatic pressing step, the processing temperature is 1500° C., the pressure is 150 MPa, and the duration is 4 hours, so as to further improve the density and mechanical strength of the ceramic.

Citation Information

Patent Citations

  • Fire-retardant coating

    CN103571287A